2007
DOI: 10.1159/000108390
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancer Screening by Colonoscopy – Current Issues

Abstract: Of all colorectal cancer screening methods, colonoscopy used as a primary screening tool is both the most promising and the most discussed in the current literature. Several countries have introduced colonoscopic screening on a national scale, but many issues still require further research. The practicality of using colonoscopic screening can be questionable given the huge target population, which requires a great increase in endoscopic resources. Limiting the target population by shifting the use of colonosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 82 publications
0
6
0
Order By: Relevance
“…Optical colonoscopy (OC) is regarded as the gold standard for colorectal tumor screening [1,2]. In recent years, it has been reported that OC is responsible for decreases in the incidence rate and mortality rate of colorectal carcinoma [3].…”
Section: Introductionmentioning
confidence: 99%
“…Optical colonoscopy (OC) is regarded as the gold standard for colorectal tumor screening [1,2]. In recent years, it has been reported that OC is responsible for decreases in the incidence rate and mortality rate of colorectal carcinoma [3].…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy with which colorectal polyps or lesions can be detected is largely associated with the cleanliness of the luminal environment 24 25. Poor cleansing is also associated with an increased risk of peritoneal contamination should perforation occur 1 2.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the fecal occult blood test, the cost of colonoscopy is significantly higher; however, it is sufficient to have it done every several years. In order to reach the true value of colonoscopy, cecal intubation is fundamental because it allows for inspection of the entire colon [1, 3, 15]. Together with the adenoma detection rate, the percentage of cecal intubation is considered to be the fundamental criterion for the evaluation of the quality of colonoscopy.…”
Section: Discussionmentioning
confidence: 99%